2021
DOI: 10.3390/diagnostics11010136
|View full text |Cite
|
Sign up to set email alerts
|

Microperimetry and Optical Coherence Tomography Changes in Type-1 Diabetes Mellitus without Retinopathy

Abstract: Background: We aimed to measure and correlate inner retinal layer (IRL) thickness and macular sensitivity by optical coherence tomography (OCT) and by microperimetry, respectively, in type 1 diabetes mellitus patients (DM1) without diabetic retinopathy (DR). Methods: Fifty-one DM1 patients and 81 age-matched healthy subjects underwent measurement of the axial length (AL), retinal thickness in the macular ETDRS areas by swept source (SS)-OCT and macular sensitivity by microperimeter. Results: The total retinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…The central inner ring of the MAIA perimetry correlated with the central macular thickness (r = − 0.347; p = 0.005). The results are similar to other studies, like Verma et al, [ 7 ] Senthil et al [ 37 ], and Orduna-Hospital et al [ 38 ], which also found a correlation between the foveal thickness and retinal sensitivity, while other authors also evaluated the relationship between retinal sensitivity and the thickness of the retinal inner layers (GCL and IPL) between healthy and patients with DM2 without DR, and did not find such a correlation [ 4 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…The central inner ring of the MAIA perimetry correlated with the central macular thickness (r = − 0.347; p = 0.005). The results are similar to other studies, like Verma et al, [ 7 ] Senthil et al [ 37 ], and Orduna-Hospital et al [ 38 ], which also found a correlation between the foveal thickness and retinal sensitivity, while other authors also evaluated the relationship between retinal sensitivity and the thickness of the retinal inner layers (GCL and IPL) between healthy and patients with DM2 without DR, and did not find such a correlation [ 4 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…Studies have also shown that mean retinal sensitivity declines with age in healthy eyes (Molina‐Martín et al, 2017; Sabates et al, 2011). While microperimetry and SD–OCT combined has been used to investigate macular structure–function relationships in AMD (Pilotto et al, 2016; Roh et al, 2019; Saßmannshausen et al, 2018; Sayegh et al, 2014; Steinberg et al, 2016; Tepelus et al, 2017; Wu et al, 2014), glaucoma (Garcia‐Medina et al, 2021) and diabetes without retinopathy (Montesano et al, 2021; Orduna‐Hospital et al, 2021), to the best of our knowledge, no prior work has tried to relate macular retinal layer thickness to mesopic visual sensitivity in younger, middle‐aged and older healthy adults.…”
Section: Introductionmentioning
confidence: 99%
“…25 Using microperimetry and OCT and/or FA, the reduction of retinal sensitivity with increasing DR severity has been well documented in conjunction with various morphologic features of DR including diabetic macular edema, reduced ganglion cell complex thickness, hard exudates, and capillary nonperfusion. [26][27][28][29][30][31][32][33][34][35][36][37] There are several recent studies comparing OCTA metrics with retinal sensitivity measured by microperimetry in diabetic retinopathy. [38][39][40][41] Although these studies report a positive association between OCTA parameters related to retinal ischemia (such as reduced vessel density and increased areas of capillary nonperfusion) and reduced MP sensitivity in DR, these comparisons have been predominantly qualitative.…”
mentioning
confidence: 99%
“…25 Using microperimetry and OCT and/or FA, the reduction of retinal sensitivity with increasing DR severity has been well documented in conjunction with various morphologic features of DR including diabetic macular edema, reduced ganglion cell complex thickness, hard exudates, and capillary nonperfusion. 26–37…”
mentioning
confidence: 99%